The psychosocial portrayals of immigrants in Spanish prime time television fiction (2016-2017) (Communication & Society, 2019)
The present research shows the results of an analysis of Spanish entertainment television aired in prime time between 2016 and the first semester of 2017 by the leading Spanish TV networks. The aim is to draw a comparison between immigrants and the natives in violent and health behaviours, personality traits, and also the number of conversation topics used by immigrants compared to the natives. Content research was used for this analysis, where a sample of 723 characters (n723) was taken. The final result shows there are different tendency patterns in the index of victims of violent behaviour being the native the ones with the highest score. No significant statistical differences in other indexes were observed. However, other variables are statistically related to immigrants/ foreigners, such as drug abuse, topics regarding health or politics, and furthermore, immigrants are also prone to have personality traits such as ‘unfair’, ‘seductive’ or ‘perverse’.